2018
DOI: 10.1002/cncr.31896
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of T‐cell subsets and the expression of immune checkpoint receptors and ligands in patients with newly diagnosed and relapsed acute myeloid leukemia

Abstract: Background Phenotypic characterization of immune cells in the bone marrow (BM) of patients with acute myeloid leukemia (AML) is lacking. Methods T‐cell infiltration was quantified on BM biopsies from 13 patients with AML, and flow cytometry was performed on BM aspirates (BMAs) from 107 patients with AML who received treatment at The University of Texas MD Anderson Cancer Center. The authors evaluated the expression of inhibitory receptors (programmed cell death protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
236
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(273 citation statements)
references
References 54 publications
(99 reference statements)
20
236
1
1
Order By: Relevance
“…Only a more recent study has reported phenotypic characterization of immune cells in the BM of patients with AML. The authors found that PD1 + /OX40 + T cells were more frequent in the BM of patients with AML, and there was a higher frequency of PD1 + CD8 + T cells coexpressed with Tim‐3 or LAG‐3 . In this study, we further investigated the frequency of CTLA‐4 and LAG‐3 coexpression with CD244 and CD57, which are common markers for evaluating T‐cell exhaustion and the immunosenescence of CD3 + , CD4 + and CD8 + T cells …”
Section: Resultsmentioning
confidence: 97%
“…Only a more recent study has reported phenotypic characterization of immune cells in the BM of patients with AML. The authors found that PD1 + /OX40 + T cells were more frequent in the BM of patients with AML, and there was a higher frequency of PD1 + CD8 + T cells coexpressed with Tim‐3 or LAG‐3 . In this study, we further investigated the frequency of CTLA‐4 and LAG‐3 coexpression with CD244 and CD57, which are common markers for evaluating T‐cell exhaustion and the immunosenescence of CD3 + , CD4 + and CD8 + T cells …”
Section: Resultsmentioning
confidence: 97%
“…Further investigation of the function of these PD‐1+Vβ+ T cells in AML and their association with disease relapse is needed. Moreover, it would be worthy to combine the detection of PD‐L1 expression in AML cells, which may be an important predicted marker for immunotherapy …”
Section: Discussionmentioning
confidence: 99%
“…However, unlike B‐cell leukemia and lymphoma, the application of immunotherapy for acute myeloid leukemia (AML) has been limited due to limited understanding of global T cell immune dysfunction in AML . Multiple aspects of T cell dysfunction including lower activation, terminal proliferation, exhaustion, and senescence are functioning in AML at diagnosis, and impairment of T cell function might be mediated by up‐regulating immune checkpoint receptors, such as programmed death‐1 (PD‐1), lymphocyte‐activation gene 3, T‐cell immunoglobulin and mucin‐domain containing‐3 (Tim‐3) . For example, CD8+ T cell dysfunction in AML was in part reversible upon PD‐1 blockade in vitro, and PD‐1 blockade could enhance CD33‐CD3 BiTE antibody construct‐mediated cytotoxicity in AML .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies characterizing T‐cell dysfunction and the cells’ reversibility with intensive chemotherapy in patients with AML have been published, but a detailed understanding of the dynamic and serial changes in the immune checkpoint molecules is lacking . In this issue of Cancer , Williams et al, in an exhaustive manner, explored the bone marrow microenvironment including, but not limited to, PD‐L1 expression and the quantity of infiltrated T cells . They assessed the T‐cell quantity in healthy versus AML bone marrow and demonstrated the expression pattern of a set of targetable coinhibitory and costimulatory receptors on T cells, and their respective ligands on the AML blasts, using multicolor flow cytometry …”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Cancer , Williams et al, in an exhaustive manner, explored the bone marrow microenvironment including, but not limited to, PD‐L1 expression and the quantity of infiltrated T cells . They assessed the T‐cell quantity in healthy versus AML bone marrow and demonstrated the expression pattern of a set of targetable coinhibitory and costimulatory receptors on T cells, and their respective ligands on the AML blasts, using multicolor flow cytometry …”
Section: Introductionmentioning
confidence: 99%